Jakob Smitsprijs 1987 : Tentoonstelling. - Jakob Smitsmuseum, Mol (Mol : VZW Jakob Smitsprijs, 1987)
De Vos, Ignace ; Blaton, Catalina ; Ong, Annette ; Molenkamp, Charlotte ; Verschoor, Frans ; Jellema, Wietse ; Van Eerdenburg, Peter ; Stolk, Joop ; Kersten, Willem Jan ; Van 't Hoenderdaal, Martinus ; Snijkers, Vera ; Swerts, Alice ; Geys, Mareike ; Dijsselbloem, Mario ; Knops, Cor ; etc.
Jakob Smitsprijs 1987, Jakob Smitsmuseum, Mol, 25 oktober tot 8 november 1987
boek